(untitled) (Research, Society and Development, 2021)
Introduction: Chagas disease is a parasitic pathology resulting from infection by the protozoan Trypanosoma cruzi, the disease is mainly transmitted by the vector form, with the insect Triatominae, commonly called the barber its main vector. It is estimated that more than 6 million people are infected with Trypanosoma cruzi worldwide. Objective: This article aimed to assess the trend of mortality from Chagas Disease in Bahia between the years 2008 to 2018, thus emphasizing the correlation of the disease with the variables: sex, age and education. Methodology: This is a retrospective ecological study, using data collected from the Mortality Information System (SIM) of the Informatics Department of the Unified Health System (DATASUS) in the health information section of the Generic Domain Tabulator. Public (TABNET). Results and Discussion: Decreasing values ​​are observed for mortality levels in Brazil due to Chagas disease. However, in the Northeast Region 11,309 deaths were registered, of which 6,856 occurred in the State of Bahia, which is considered a worrying factor since the Northeast Region has 9 states and only Bahia had more than 50% of deaths from Chagas Disease that succeeded in that region. Conclusion: By observing the analyzed data, it can be seen that Bahia has a high mortality trend due to Chagas disease, a fact that is correlated with the sex, age group and education of individuals who died from this disease.